The Effects of Audit Quality Disclosure on Audit Effort and Investment Efficiency - Chen, Qi; Jiang, Xu; Zhang, Yun (The Accounting Review, 2019)
ABSTRACT We develop a model to evaluate the costs and benefits of disclosing information about audit quality. Specifically, we examine whether audit quality disclosure affects auditors' effort and investors' investment efficiency. In our setting, an auditor exerts unobservable effort to influence audit quality and is motivated by liability in the event of audit failure. The usefulness of audited financial reports for investors depends on both the quality of the underlying financial reporting (e.g., as embodied by GAAP) and the quality of auditors' reports (i.e., the likelihood with which audit evidence uncovers managerial misreporting). We show that audit quality disclosure increases auditors' effort incentives if and only if the underlying financial reporting quality is relatively weak. We also show that such disclosure can actually reduce investment efficiency. Our analyses contribute to the debate about policies aimed at improving audit transparency.